Clinical, genetic profile and therapy evaluation of 11 Chinese pediatric patients with Fanconi-Bickel syndrome - Taozi Du; Yu Xia; Chengkai Sun; Zhuwen Gong; Lili Liang; Zizhen Gong; Ruifang Wang; Deyun Lu; Kaichuang Zhang; Yi Yang; Yuning Sun; Manqing Sun; et al. (Orphanet Journal of Rare Diseases, 2024)
Abstract Background Fanconi-Bickel syndrome (FBS) is a rare autosomal recessive disorder characterized by impaired glucose and galactose utilization as well as proximal renal tubular dysfunction. Methods Clinical, biochemical, genetic, treatment, and follow-up data for 11 pediatric patients with FBS were retrospectively analysed. Results Hepatomegaly (10/11), short stature (10/11) and hypophosphataemic rickets (7/11) were the most common initial symptoms. At diagnosis, all patients had decreased fasting blood glucose (FBG), plasma bicarbonate (HCO3 −) and serum phosphorus, as well as elevated liver transaminases, alkaline phosphatase (AKP) and proximal renal tubular dysfunction. Two infant patients were misdiagnosed with transient neonatal diabetes mellitus. After therapy with uncooked cornstarch and conventional rickets treatment, remission of hepatomegaly was observed in all patients, with significant improvements in pre-prandial blood glucose, liver transaminases, triglyceride, plasma HCO3 − and AKP (p < 0.05). At the last follow-up, 5/7 patients with elevated AKP had nephrocalcinosis. The mean height standard deviation score (Ht SDS) of eight patients with regular treatment increased from − 4.1 to -3.5 (p = 0.02). Recombinant human growth hormone (rhGH) was administered to 4/9 patients, but their Ht SDS did not improve significantly (p = 0.13). Fourteen variants of the SLC2A2 gene were identified, with six being novel, among which one was recurrent: c.1217T > G (p.L406R) (allele frequency: 4/22, 18%). Patients with biallelic missense variants showed milder metabolic acidosis than those with null variants. Two of five patients from nonconsanguineous families with rare homozygous variations showed 5.3 Mb and 36.6 Mb of homozygosity surrounding the variants, respectively; a region of homozygosity (ROH) involving the entire chromosome 3 covering the SLC2A2 gene, suggesting uniparental disomy 3, was detected in one patient. Conclusions Early diagnosis of FBS is difficult due to the heterogeneity of initial symptoms. Although short stature is a major issue of treatment for FBS, rhGH is not recommended in FBS patients who have normal GH stimulation tests. Patients with biallelic null variants may require alkali supplementation since urine bicarbonate loss is genetically related. ROH is a mechanism for rare homozygous variants of FBS in nonconsanguineous families.